Analysis of the Role of Zakat in Eradicating Poverty (Case Study of the Medan City Yatim Mandiri Foundation) - Sartika, Sartika; Rokan, Mustapa Khamal; Nasution, Juliana (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Poverty is a major problem that is certainly experienced in a developing country, one of which is Indonesia. This means that poverty is a condition where someone cannot meet their basic needs. Welfare is something that can be felt by someone in their life where they feel their life is fulfilled and sufficient without any burden and pressure. This study aims to determine the role of zakat as a tool or intermediary in poverty alleviation in the city of Medan. This research method uses a qualitative method with a descriptive analysis approach. The type of data collected uses interview data at the Yatim Mandiri foundation in the city of Medan. The results of the study revealed that the Laznas Yatim Mandiri zakat program in the city of Medan has proven effective in improving the welfare of mustahik. With a collaborative approach between education, health, and economic empowerment, this foundation has succeeded in improving the standard of living of mustahik and reducing poverty.